In-field measurement of vertical and horizontal forces in ski-jumping: Evaluation of a portable two-dimensional force plate - Fritz, J.; Kröll, J.; Jenny, H.; Schwameder, H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Various methods for measuring ground reaction forces during ski-jumping have been developed and applied. The main limitations of the current systems are the restriction to the measurement of single phases (parts of the in-run and take-off) and single force components (vertical component only). Therefore, the purpose of this study was to assess a recently developed force measurement system (JH-SJ), which records forces in the vertical (compression and tension) and horizontal (anterior and posterior) directions over the entire hill jumping sequence. Comparing the values between the JH-SJ and calibrated reference systems in a static and ski-jumping-specific condition provided a means of validating the use of JH-SJ. Hill jumps were performed to evaluate the system regarding the feasibility of application and plausibility of the obtained data. Mean absolute difference during static validity evaluation was 3.5?N (2.7%). Root mean square errors during ski-jumping-specific validity evaluation were less than 11.9?N. Vertical forces acted as compression during all phases of the hill jump except for the flight phase, when tension forces were also recorded. Horizontal force acted as friction on the system during in-run, take-off and landing. The small deviation of the measurement system compared to the reference systems suggests high validity of the JH-SJ measurement system. Qualitative analysis of the forces during hill jumps delivered plausible results for all phases, similar to previous studies. Based on this study, the JH-SJ system measures forces with a high degree of accuracy and precision in real conditions (hill jumps), while contributing new insights into ski-jumping kinetics.